How to Convert a Flavor of Quantum Bit Commitment - Crépeau, Claude; Légaré, Frédéric; Salvail, Louis (BRICS Report Series, 2000)
In this paper we show how to convert a statistically binding but computationally concealing quantum bit commitment scheme into a computationally binding but statistically concealing scheme. For a security parameter n, the construction of the statistically concealing scheme requires O(n^2) executions of the statistically binding scheme. As a consequence, statistically concealing but computationally binding quantum bit commitments can be based upon any family of quantum one-way functions. Such a construction is not known to exist in the classical world.